The Role of Job Crafting and Perceived Organizational Support on Millennial Work Engagement - R. Mahendra Wijaya Santoso; Noor Siti Rahmani (Faculty of Psychology, Universitas Negeri Yogyakarta, 2025)
The organization should prioritize and improve employee engagement if the organization wants to effectively realize their goals and objectives. This study examines the impact of work engagement predicted by job crafting and perceived organizational support on millennials working in startup companies. This study proposes a hypothesis that job crafting and perceived organizational support have a positive role in predicting work engagement. Respondent are 162 employees working in various startup companies in Indonesia that must fill the scale of job crafting and perceived organizational support. Data was analyzed by multiple regression analysis. These results prove the research hypothesis which states that job crafting and perceived organizational support together have a positive role on work involvement can be accepted. Job crafting and perceived organizational support together contributed 40.9% in influencing work engagement.